Negative electrode sheet and electrochemical device and electronic device containing the same

By using a three-dimensional skeleton porous layer composed of electrical insulating fibers in the negative electrode sheet of the lithium-ion battery, the problem of volume change in lithium metal during charging and discharging and lithium dendrites is solved, and the circulation performance and safety of the battery are improved.

CN115280550BActive Publication Date: 2025-03-14NINGDE AMPEREX TECHNOLOGY LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202180017969.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-07-09
Publication Date
2025-03-14
Estimated Expiration
2041-07-09

AI Technical Summary

Technical Problem

In lithium-ion batteries, the pure lithium metal electrode lacks a porous structure, resulting in severe volume changes in the lithium metal during charging and discharging, forming lithium dendrites and dead lithium, reducing battery capacity and bringing safety risks.

Method used

A three-dimensional skeleton porous layer containing electrical insulating fibers is used as the structure of the negative electrode sheet. A three-dimensional skeleton is prepared by electrospinning technology, and a porous layer is provided on the negative electrode current collector to control the deposition of lithium metal and suppress volume expansion.

Benefits of technology

It effectively improves the deposition morphology of lithium metal, inhibits the growth of lithium dendrites, and improves the circulation, capacity and safety performance of electrochemical devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115280550B_ABST
    Figure CN115280550B_ABST
Patent Text Reader

Abstract

The present application relates to a negative electrode plate and an electrochemical device and an electronic device containing the same. The present application provides a negative electrode plate, which includes: a negative electrode current collector and a porous layer. The porous layer is located on the negative electrode current collector, and the porous layer includes a three-dimensional skeleton containing electrically insulating fibers. The three-dimensional skeleton is configured to accommodate lithium metal deposition. The negative electrode of the present application can effectively improve the lithium metal deposition on the surface of the negative electrode during the charge and discharge cycle of the electrochemical device by providing a porous layer including a three-dimensional skeleton and using an electrically insulating three-dimensional skeleton material; and inhibit the volume expansion of lithium metal; while slowing down the growth of lithium dendrites, thereby improving the cycle performance, capacity performance and safety performance of the electrochemical device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of energy storage, and specifically to a negative electrode plate comprising a three-dimensional skeleton structure and an electrochemical device and an electronic device comprising the negative electrode plate, in particular a lithium-ion battery. Background Art

[0002] With the development of technology and the increase in demand for mobile devices, people's demand for electrochemical devices (such as lithium-ion batteries) has increased significantly. Lithium metal is one of the metals with the highest mass-to-energy ratio discovered so far. Lithium-ion batteries using lithium metal as negative electrode materials can greatly improve the energy density and operating voltage of electrochemical devices.

[0003] In the actual use of electrochemical devices, there are at least the following problems with directly using lithium metal as the negative electrode material: 1) Lithium metal is prone to side reactions with substances in the electrolyte, resulting in the consumption of the electrolyte and fresh lithium metal, thereby reducing the coulombic efficiency; 2) During the charging and discharging process of lithium metal, the deposition and dissolution of lithium metal will be uneven due to the uneven distribution of lithium metal surface potential and the uneven distribution of lithium ion concentration in the electrolyte, thereby forming "lithium dendrites" and "dead lithium". The formation of lithium dendrites and dead lithium will further reduce the battery capacity. In severe cases, lithium dendrites can pierce the diaphragm and cause the battery to short circuit, posing a safety risk; 3) As the battery continues to charge and discharge, the lithium metal precipitate will continue to expand and shrink in volume, causing damage to the electrode structure. In severe cases, it will cause the interface between the negative electrode plate and the less flexible inorganic protective coating to peel off, thereby losing the protective effect.

[0004] In view of this, it is indeed necessary to study and improve the electrode plates to enhance the safety of their use in electrochemical devices and electronic devices. Summary of the invention

[0005] The embodiments of the present application provide an electrode sheet that improves the safety of an electrode assembly and an electrochemical device comprising the same to at least some extent solve at least one problem existing in the related art.

[0006] In one aspect of the present application, the present application provides a negative electrode sheet, comprising: a negative electrode current collector and a porous layer. The porous layer is located on the negative electrode current collector, and the porous layer comprises a three-dimensional skeleton containing electrically insulating fibers. The three-dimensional skeleton is configured to accommodate lithium metal deposition.

[0007] In another aspect of the present application, the present application provides an electrochemical device, which includes the positive electrode in the above embodiment.

[0008] The negative electrode of the present application is provided with a porous layer including a three-dimensional skeleton, and the three-dimensional skeleton is composed of electrically insulating fibers, which can effectively improve the lithium metal deposition on the negative electrode surface during the charge and discharge cycle of the electrochemical device; and inhibit the volume expansion of lithium metal; and at the same time slow down the growth of lithium dendrites, thereby improving the cycle performance, capacity performance and safety performance of the electrochemical device. When the electrochemical device of the present application is charged, the three-dimensional skeleton with electrically insulating fibers can block the transmission of electrons from the negative electrode current collector side to the porous layer surface, realize the control of the direction and position of lithium metal deposition, and further improve the volume expansion and cycle stability of the pole piece.

[0009] In another aspect of the present application, the present application provides an electronic device, which includes the above-mentioned electrochemical device.

[0010] Additional aspects and advantages of the embodiments of the present application will be described, shown, or explained in part in the subsequent description through implementation of the embodiments of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] The following will briefly describe the drawings necessary for describing the embodiments of the present application or the prior art to facilitate the description of the embodiments of the present application. Obviously, the drawings described below are only some of the embodiments in the present application. For those skilled in the art, without the need for creative work, drawings of other embodiments can still be obtained based on the structures illustrated in these drawings.

[0012] Figure 1 Schematic diagram of the structure of the negative electrode according to some embodiments of the present application.

[0013] Figure 2 Schematic diagram of the cross-sectional structure of the negative electrode according to some embodiments of the present application.

[0014] Figure 3 1 is a scanning electron microscope (SEM) image of a top view of a three-dimensional skeleton according to some embodiments of the present application.

[0015] Figure 4 is a scanning electron microscope image of lithium metal deposition in a porous layer according to some embodiments of the present application.

[0016] Figure 5 Schematic diagram of the structure of a hollow structure fiber according to some embodiments of the present application.

[0017] Figure 6 This is the molecular structure diagram of the β phase of polyvinylidene fluoride.

[0018] Figure 7 Schematic diagram of the structure of the negative electrode according to other embodiments of the present application. DETAILED DESCRIPTION

[0019] The embodiments of the present application will be described in detail below. The embodiments of the present application should not be interpreted as limiting the present application.

[0020] Unless expressly stated otherwise, the following terms used herein have the meanings indicated below.

[0021] As used herein, the terms "substantially," "substantially," "essentially," and "about" are used to describe and illustrate small variations. When used in conjunction with an event or circumstance, the terms may refer to instances where the event or circumstance occurred exactly as well as instances where the event or circumstance occurred very approximately. For example, when used in conjunction with a numerical value, the terms may refer to a range of variation less than or equal to ±10% of the numerical value, such as less than or equal to ±5%, less than or equal to ±4%, less than or equal to ±3%, less than or equal to ±2%, less than or equal to ±1%, less than or equal to ±0.5%, less than or equal to ±0.1%, or less than or equal to ±0.05%. For example, two values ​​may be considered “substantially” the same if the difference between them is less than or equal to ±10% of the average of the values ​​(e.g., less than or equal to ±5%, less than or equal to ±4%, less than or equal to ±3%, less than or equal to ±2%, less than or equal to ±1%, less than or equal to ±0.5%, less than or equal to ±0.1%, or less than or equal to ±0.05%).

[0022] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.

[0023] Furthermore, for ease of description, "first", "second", "third", etc. may be used herein to distinguish different components of one figure or a series of figures. Unless otherwise specifically specified or limited, "first", "second", "third", etc. are not intended to describe corresponding components.

[0024] Lithium metal is the metal with the smallest relative atomic mass (6.94) and the lowest standard electrode potential (-3.045V) among all metal elements, and its theoretical specific capacity is as high as 3860mAh / g. In theory, using lithium metal as the negative electrode active material can increase the working voltage and capacity of the electrochemical device. However, the current lithium-ion batteries are mainly faced with the following difficulties: First, the commonly used negative electrode materials of lithium-ion batteries, such as graphite, exist in the graphite layer structure in the form of embedded lithium ions during charging. The graphite layer has a porous structure that provides storage space for lithium metal. For pure lithium metal electrodes, there is no such porous structure, so there will be a very drastic volume change during the charging and discharging process, which leads to a series of problems affecting the battery's cycle performance; secondly, due to the uneven current density and lithium ion concentration in the electrolyte, the deposition speed of some sites will be too fast during the deposition process, and then a sharp dendrite structure will be formed. The presence of lithium dendrites will greatly reduce the deposition density, resulting in a decrease in energy density. At present, in some lithium metal batteries, the actual deposition density of lithium metal is about 0.2g / cc, which is much lower than the true density of lithium metal 0.534g / cc. The energy density will be reduced by more than 100Wh / L due to the loose deposition of lithium metal. In addition, lithium dendrites may pierce the diaphragm to form a short circuit, causing safety problems.

[0025] Figure 1 and Figure 2 It is a schematic diagram and a cross-sectional schematic diagram of the negative electrode according to some embodiments of the present application.

[0026] According to one aspect of the present application, Figure 1 and Figure 2 As shown, the embodiment of the present application provides a negative electrode 10, which is provided with a porous layer 101 including a three-dimensional skeleton on the surface of the negative electrode current collector 100, providing a host for lithium metal, ensuring that during the charge and discharge process of the battery, the lithium metal can be stored in the three-dimensional skeleton in the porous layer on the surface of the current collector, thereby inhibiting volume expansion, and at the same time, the three-dimensional skeleton can improve the deposition morphology of lithium metal and inhibit the formation of lithium dendrites. In some embodiments, the porous layer 101 is entirely composed of the three-dimensional skeleton.

[0027] In some embodiments, the material of the three-dimensional skeleton in the porous layer 101 includes electrically insulating fibers. The electrically insulating fibers can prevent electrons from migrating from the surface of the negative electrode current collector to the outer surface of the porous layer, thereby inducing lithium metal to gradually deposit from the surface side of the negative electrode current collector to the inside of the porous layer, further improving the volume expansion of the negative electrode, inhibiting the growth of lithium dendrites, and thus improving the cycle performance of the electrochemical device. In some embodiments, the three-dimensional skeleton is entirely composed of electrically insulating fibers.

[0028] It should be understood by those skilled in the art that the term "electrically insulating" herein does not mean that it is completely unable to conduct electrons, but rather means that it has extremely low electronic conductivity (conductivity). In some embodiments, the electrical conductivity of the electrically insulating fibers included in the three-dimensional framework is less than 10 -10 S / cm.

[0029] Figure 3 and Figure 4 The top view of the three-dimensional skeleton and the scanning electron microscope images of lithium metal deposition in the porous layer according to some embodiments of the present application are shown respectively. Figure 3 and 4 As shown in , by controlling the electron non-conduction of the three-dimensional skeleton in the porous layer, the deposition direction of lithium metal can be controlled, and the lithium metal can be completely deposited inside the porous layer, improving the expansion and cycle stability of the negative electrode.

[0030] In some embodiments, the structure of the electrically insulating fiber can include strip fibers, spherical fibers, and block fibers. In some embodiments, the fiber structure is a strip fiber, wherein a three-dimensional skeleton is constructed by a plurality of single strip fibers and strip fibers, and the material of the strip fiber can better construct a three-dimensional skeleton to form a self-supporting structure.

[0031] In some embodiments, the diameter of the fiber is 50 nm to 10 μm. In other embodiments, the diameter of a single fiber is approximately, for example, about 50 nm, about 100 nm, about 200 nm, about 300 nm, about 400 nm, about 500 nm, about 700 nm, about 1 μm, about 2 μm, about 5 μm, about 10 μm, or a range consisting of any two of these values. In some embodiments, the diameter of a single fiber is 200 nm to 2 μm.

[0032] In some embodiments, the porosity of the porous layer is greater than or equal to 70% or 80%. In other embodiments, the porosity of the porous layer is 70% to 90% to ensure that there is enough space in the porous layer to accommodate lithium metal deposition and maintain a certain structural strength and stability.

[0033] In some embodiments, the porous layer contains holes formed by the fibers in the three-dimensional skeleton being built together, and the holes are formed between the fibers. In some embodiments, the fibers in the three-dimensional skeleton are interwoven to form holes, and the hole size range is approximately 100nm to 10μm. In other embodiments, the size of the holes formed by the interweaving of the fibers in the three-dimensional skeleton is approximately, for example, about 100nm, about 200nm, about 500nm, about 1μm, about 2μm, about 5μm, about 10μm or a range consisting of any two of these values. In some embodiments, the holes formed by the strip fibers and the strip fibers building each other have a more consistent hole distribution range, and their hole structure is more stable, which can improve the deposition law of lithium metal and inhibit the formation of irregular lithium dendrites. In some embodiments, the hole size range formed by the interweaving of the fibers in the three-dimensional skeleton is 500nm to 5μm.

[0034] In addition to being defined by the shape structure, the fiber can also be defined by the pore structure of the fiber itself, which can include a solid structure, a hollow structure, or both. A solid structure means that the fiber itself does not have any holes, while a hollow structure represents that the fiber itself has a pore structure. In some embodiments, the fiber in the three-dimensional skeleton has a hollow structure, and the porous layer contains holes in the fiber itself, which are formed inside the fiber. In some embodiments, the pore size of the hollow structure is 10nm to 500nm. In other embodiments, the pore size of the hollow structure is approximately, for example, about 10nm, about 50nm, about 200nm, about 500nm, or a range consisting of any two of these values.

[0035] Figure 5 Schematic diagram of the structure of a hollow structure fiber according to some embodiments of the present application.

[0036] In some embodiments, Figure 5 As shown, the pore structure of the hollow structure fiber can be in three forms, including a hollow structure, a pore structure on the wall, or a hollow and pore structure on the wall. In some embodiments, when the fiber is a hollow structure, the fiber wall thickness of the fiber is 50nm to 4.5μm. In some embodiments, when the fiber is a pore structure on the wall, the size of the pores of the pore structure on the wall is 50nm to 500nm. When the fiber has a hollow structure, including a hollow structure or a pore structure on the wall, the transmission rate of the electrolyte in the three-dimensional skeleton can be accelerated; at the same time, the design of the hollow structure can further reduce the structural weight of the three-dimensional skeleton, improve the surface utilization of lithium metal in the three-dimensional skeleton, and also help to improve the overall energy density of the electrochemical device.

[0037] In some embodiments, the fibers include ion conductor fibers, in which lithium ions can combine with some active groups on the surface of the ion conductor fibers to form an association. As the fiber surface moves, the active sites of the lithium ion association can continuously move and transform, thereby achieving the transmission of lithium ions and further improving the lithium ion transmission efficiency in the porous layer.

[0038] In some embodiments, the material of the fiber includes one or more of a polymer material and an inorganic material, wherein the polymer material includes one or more of the following components and derivatives of each component: polyvinylidene fluoride, polyimide, polyamide, polyacrylonitrile, polyethylene glycol, polyphenylene ether, polypropylene carbonate, polymethyl methacrylate, polyethylene terephthalate, polyethylene oxide, polyvinylidene fluoride-hexafluoropropylene or polyvinylidene fluoride-chlorotrifluoroethylene; and the inorganic material includes, but is not limited to, one or more of the following components and derivatives of each component: sodium silicate, aluminum oxide or silicon oxide.

[0039] In some embodiments, the fiber includes a material having piezoelectricity. The term "material having piezoelectricity" herein refers to a material that is an electrical insulator at normal pressure, but when a certain range of pressure is applied to it, changes in its internal structure allow current to pass through it. Materials having piezoelectricity can exhibit a high dielectric constant of more than 100, and when a certain range of pressure is applied to stretch or compress them, they are positively charged on one surface and negatively charged on the other surface. Therefore, when the negative electrode is charged, the three-dimensional skeleton will further expand and stretch due to the deposition of lithium metal in the porous layer, wherein the fiber using the piezoelectric material can generate a potential difference between the two surfaces of the lithium ion metal deposition area in the porous layer, thereby increasing the electrical conductivity of the three-dimensional skeleton between the lithium ion metal deposition areas, thereby improving the electrical cycle effect of the negative electrode, and optimizing the density and direction of lithium metal deposition. In some embodiments, the piezoelectric material includes, but is not limited to, BaTiO3, Pb(Zr, Ti)O3 (PZT), Pb 1-x La x Zr 1-y Ti y O3(PLZT), PB(Mg3Nb 2 / 3 )O3-PbTiO3 (PMN-PT), hafnium dioxide (HfO2) or one or more thereof.

[0040] In some embodiments, the fiber includes a fluorine-containing polymer having a β phase. The term "β phase" herein refers to a thermodynamically stable phase in a crystal phase stacking structure of a polymer material. For example, when polyvinylidene fluoride is used as a fiber with a three-dimensional skeleton, polyvinylidene fluoride has five crystal phases, αβγδε, the most common of which is the αβγ phase, the α phase is a kinetically controlled phase, and the β phase is a thermodynamically stable phase. Figure 6As shown, the HFC atoms in the β phase of the fluorinated polymer fiber (for example, but not limited to, polyvinylidene fluoride) present an orderly folded arrangement, resulting in the dipole moment pointing in the same direction, and its monomer unit has the highest dipole moment relative to other phases, so the β phase has better piezoelectricity, thermoelectricity and ferroelectricity. In the present application, the β phase in the fluorinated polymer fiber can be effectively improved by improving the preparation process, and by adding the β phase fluorinated polymer fiber to the fiber of the three-dimensional skeleton, the stacking structure of the polymer material in the fiber is optimized to make it have good piezoelectric properties, thereby improving the deposition of lithium metal.

[0041] In this paper, the stacking structure of the fibers used in the three-dimensional framework can be tested by Fourier transform infrared spectroscopy (FTIR) to determine the crystalline phase of the stacking structure of the polymer material in the fibers.

[0042] In some embodiments, the maximum deposition amount M of lithium metal per unit volume of the three-dimensional skeleton of the present application meets the following formula: M = T / 4.85 (mAh / cm 3 ), where T is the thickness of the three-dimensional skeleton. In some embodiments, the deposition density of lithium metal in the three-dimensional skeleton can reach 0.534 g / cm 3 .

[0043] In some embodiments, the thickness of the porous layer is 30 μm to 500 μm. In other embodiments, the thickness of the porous layer is approximately, for example, about 30 μm, about 40 μm, about 50 μm, about 60 μm, about 70 μm, about 80 μm, about 90 μm, about 100 μm, about 200 μm, about 250 μm, about 300 μm, about 400 μm, about 500 μm, or a range consisting of any two of these values. In some embodiments, the thickness of the porous layer is 300 μm to 500 μm. The thickness of the porous layer can provide a stable pore utilization rate, increase the deposition amount of lithium metal in the electrochemical device, and thus provide a high-capacity electrochemical device.

[0044] In some embodiments, the porous layer in the negative electrode can be treated with pre-lithium supplementation to improve the lithium capacity and cycle performance of the electrochemical device. The pre-lithium supplementation treatment can be performed by one or more of the following processes: cold pressing, hot pressing, electrochemical lithium supplementation, or physical vapor deposition (PVD). In some embodiments, the lithium metal pre-supplemented in the negative electrode can be disposed inside the porous layer or between the porous layer and the negative electrode current collector.

[0045] Figure 7 Schematic diagram of the structure of the negative electrode according to other embodiments of the present application.

[0046] like Figure 7As shown, in some embodiments, the negative electrode 10 can further include lithium metal 102, wherein the lithium metal is disposed between the porous layer and the negative electrode current collector, as a supplementary lithium metal to enhance the energy density of the electrochemical device. In some embodiments, the thickness of the lithium metal is equal to or less than 50 μm. In some embodiments, the thickness of the lithium metal is equal to or less than 30 μm, so that the electrochemical device obtains the best energy density.

[0047] In some embodiments, the negative electrode current collector may be a copper foil or a nickel foil. However, other materials commonly used in the art may be used as the negative electrode current collector without limitation.

[0048] According to another aspect of the present application, an embodiment of the present application provides a method for preparing a negative electrode, which comprises the following steps: preparing an electrically insulating three-dimensional skeleton by electrospinning technology, and then arranging a porous layer composed of the three-dimensional skeleton on the negative electrode current collector by a cold pressing process. Finally, the negative electrode is obtained by a cutting process.

[0049] In some embodiments, in the preparation process of electrospinning technology, the present application further changes the precursor solution and adds acetone to the solvent N,N-dimethylformamide, wherein the content of acetone is 10wt% to 20wt% based on the total amount of the precursor solution to increase the β-phase content of the fluoropolymer in the fiber of the three-dimensional skeleton. In some embodiments, in the preparation process of electrospinning technology, the present application increases the rotation speed of the drum to 1500rpm to 2500rpm, increases the electric field stretching force, and can also provide the β-phase content of the fluoropolymer in the fiber of the three-dimensional skeleton. In some embodiments, in the preparation process of electrospinning technology, the present application increases the range of the distance between the collection plate and the needle to 15cm to 20cm, which can increase the solvent evaporation rate and further increase the β-phase content.

[0050] According to another aspect of the present application, an embodiment of the present application provides an electrochemical device, the electrochemical device comprising a positive electrode, a separator, and a negative electrode provided in the above embodiments. In some embodiments, the electrochemical device is a lithium-ion battery.

[0051] In some embodiments, when the electrochemical device is fully charged, the thickness t of the portion where the lithium metal is deposited is at least greater than or equal to 30% of the thickness T of the porous layer. It should be understood that the porous layer of the negative electrode in the present application will expand or decrease in volume as the lithium metal is deposited during the charge and discharge cycle. Therefore, the "thickness T" of the porous layer in this article is the thickness of the porous layer when the electrochemical device is fully charged. By limiting the thickness t of the portion where the lithium metal is deposited to be at least greater than or equal to 30% of the thickness T of the porous layer, the present application can alleviate the volume expansion of the negative electrode or porous layer in the electrochemical device, thereby improving the full battery cycle performance; at the same time, increasing the utilization rate of the lithium metal deposition in the porous layer can further ensure the overall energy density of the electrochemical device.

[0052] It should be understood that in the electrochemical device, the thickness T of the porous layer in the negative electrode and the thickness t of the lithium metal deposition part can be tested by the common thickness test method in the art without being limited thereto. In some embodiments, the thickness test method for the porous layer of the negative electrode and its lithium metal deposition part is as follows: a positive electrode with lithium iron phosphate positive electrode material and a negative electrode with a porous layer in the above embodiment are used to form an electrochemical device by a single-layer stacking method. The electrochemical device is cycled multiple times and the discharge capacity of each cycle is recorded; when the discharge capacity of the electrochemical device is reduced to 80%, the cycle is stopped and the electrochemical device is charged to a full charge state; then the battery is disassembled, the negative electrode plate is taken out, and it is immersed in a dimethyl carbonate solution, and a sample of the negative electrode plate is prepared by an argon ion polishing CP method, and a scanning electron microscope is used to observe the cross section of the negative electrode plate, and the thickness T of the porous layer in the negative electrode and the thickness t of the lithium metal deposition part are recorded. In some embodiments, the electrochemical device is cycled one or more times as follows: in a constant temperature environment of 20°C, the device is charged to 3.7V at a constant current rate of 0.2C, then charged to 0.025C at a constant voltage, and allowed to stand for 5 minutes; subsequently, the device is discharged to 2.55V at a constant current of 0.5C, and allowed to stand for 5 minutes, which is one cycle.

[0053] In some embodiments, the positive electrode comprises a positive electrode current collector, which may be an aluminum foil or a nickel foil, however, other positive electrode current collectors commonly used in the art may be used without limitation.

[0054] In some embodiments, the positive electrode includes a positive electrode active material layer. The positive electrode active material layer includes a positive electrode active material capable of absorbing and releasing lithium (Li) (hereinafter, sometimes referred to as "a positive electrode active material capable of absorbing / releasing lithium Li"). Examples of positive electrode active materials capable of absorbing / releasing lithium (Li) may include lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium manganese oxide, lithium iron manganese phosphate, lithium vanadium phosphate, lithium vanadium phosphate, lithium iron phosphate, lithium titanate, and one or more of lithium-rich manganese-based materials.

[0055] In the above-mentioned positive electrode active materials, the chemical formula of lithium cobalt oxide can be Li y Co a M1 b O 2-c , wherein M1 represents at least one selected from nickel (Ni), manganese (Mn), magnesium (Mg), aluminum (Al), boron (B), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), copper (Cu), zinc (Zn), molybdenum (Mo), tin (Sn), calcium (Ca), strontium (Sr), tungsten (W), yttrium (Y), lanthanum (La), zirconium (Zr) and silicon (Si), and the values ​​of y, a, b and c are respectively in the following ranges: 0.8≤y≤1.2, 0.8≤a≤1, 0≤b≤0.2, -0.1≤c≤0.2;

[0056] In the above-mentioned positive electrode active material, the chemical formula of lithium nickel cobalt manganese oxide or lithium nickel cobalt aluminum oxide can be Li z Ni d M2 e O 2-f , wherein M2 represents at least one selected from cobalt (Co), manganese (Mn), magnesium (Mg), aluminum (Al), boron (B), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), copper (Cu), zinc (Zn), molybdenum (Mo), tin (Sn), calcium (Ca), strontium (Sr), tungsten (W), zirconium (Zr) and silicon (Si), and the values ​​of z, d, e and f are respectively in the following ranges: 0.8≤z≤1.2, 0.3≤d≤0.98, 0.02≤e≤0.7, -0.1≤f≤0.2;

[0057] Among the above-mentioned positive electrode active materials, the chemical formula of lithium manganese oxide is Li u Mn 2-g M 3g O 4-h , wherein M3 represents at least one selected from cobalt (Co), nickel (Ni), magnesium (Mg), aluminum (Al), boron (B), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), copper (Cu), zinc (Zn), molybdenum (Mo), tin (Sn), calcium (Ca), strontium (Sr) and tungsten (W), and the values ​​of u, g and h are respectively in the following ranges: 0.8≤u≤1.2, 0≤g<1.0 and -0.2≤h≤0.2.

[0058] Among the above-mentioned positive electrode active materials, the chemical formula of lithium iron phosphate is LiFePO4.

[0059] In some embodiments, the positive electrode active material layer can further include at least one of a binder and a conductive agent. It should be understood that those skilled in the art can select conventional binders and conductive agents in the art according to actual needs without being limited thereto.

[0060] In some embodiments, the separator includes, but is not limited to, at least one selected from polyethylene, polypropylene, polyethylene terephthalate, polyimide and aramid. For example, polyethylene includes at least one component selected from high-density polyethylene, low-density polyethylene and ultra-high molecular weight polyethylene. In particular, polyethylene and polypropylene have a good effect on preventing short circuits and can improve the stability of the battery through the shutdown effect. It should be understood that those skilled in the art can select a conventional separator in the art according to actual needs without being limited thereto.

[0061] The lithium-ion battery of the present application further comprises an electrolyte, which comprises a lithium salt and a non-aqueous solvent.

[0062] In some embodiments, the lithium salt is selected from one or more of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, LiSiF6, LiBOB and lithium difluoroborate. For example, the lithium salt is selected from LiPF6 because it can provide high ionic conductivity and improve cycle characteristics.

[0063] The non-aqueous solvent may be a carbonate compound, a carboxylate compound, an ether compound, other organic solvents or any combination thereof.

[0064] The carbonate compound may be a linear carbonate compound, a cyclic carbonate compound, a fluorinated carbonate compound or any combination thereof.

[0065] Examples of the above other organic solvents are dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate, and phosphoric acid esters and any combination thereof.

[0066] In some embodiments, the non-aqueous solvent is selected from the group consisting of ethylene carbonate, propylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, propylene carbonate, methyl acetate, ethyl propionate, fluoroethylene carbonate, and any combination thereof.

[0067] In some embodiments, the non-aqueous solvent is a mixture of dioxolane (DOL) and dimethyl ether (DME) in a volume ratio of 0.5-2.

[0068] It should be understood that the preparation methods of the positive electrode, separator and electrolyte in the embodiments of the present application can be selected according to specific needs by any suitable conventional method in the art without violating the spirit of the present application, without being limited thereto. In one embodiment of the method for manufacturing an electrochemical device, the preparation method of a lithium-ion battery comprises: winding, folding or stacking the negative electrode, separator and positive electrode in the above embodiments in sequence into an electrode assembly, placing the electrode assembly in, for example, an aluminum-plastic film, and injecting an electrolyte, followed by vacuum packaging, standing, forming, shaping and other processes to obtain a lithium-ion battery.

[0069] Although lithium ion batteries are used as examples above, those skilled in the art will be able to imagine that the bonding layer of the present application can be used for other suitable electrochemical devices after reading the present application. Such an electrochemical device includes any device in which an electrochemical reaction occurs, and its specific examples include all kinds of primary batteries, secondary batteries, fuel cells, solar cells or capacitors. In particular, the electrochemical device is a lithium secondary battery, including a lithium metal secondary battery, a lithium ion secondary battery, a lithium polymer secondary battery or a lithium ion polymer secondary battery.

[0070] Some embodiments of the present application further provide an electronic device, which includes the electrochemical device in the embodiments of the present application.

[0071] The electronic device of the embodiment of the present application is not particularly limited, and it can be any electronic device known in the prior art. In some embodiments, the electronic device may include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc. Specific embodiments

[0073] Some specific embodiments and comparative examples are listed below, and the electrochemical devices (lithium-ion batteries) thereof are subjected to lithium metal deposition tests, cycle performance tests, and cycle thickness expansion rate tests to better illustrate the technical solution of the present application.

[0074] 1. Test Method

[0075] 1.1 Lithium metal deposition test:

[0076] The lithium-ion batteries of the following examples and comparative examples were placed in a thermostat at 25°C ± 2°C for 2 hours, and discharged at a constant current of 0.5C to 3.00V. After standing for 5 minutes, they were charged at a constant current of 0.7C to 4.45V, and then charged at a constant voltage of 4.45V to 0.02C. This is one lithium metal deposition test cycle. After repeating the above lithium metal deposition test cycle 10 times, the fully charged lithium-ion battery was disassembled and the lithium metal deposition position was recorded.

[0077] 1.2 Cycle performance test:

[0078] The lithium ion batteries formed in the following examples and comparative examples were placed in a constant temperature box at 25°C ± 2°C for 2 hours, charged to 4.45V at a constant current of 0.7C, then charged to 0.05C at a constant voltage of 4.45V and left to stand for 15 minutes; then discharged to 3.0V at a constant current of 0.5C, which was one charge and discharge cycle process, and the discharge capacity of the lithium ion battery in the first cycle was recorded; then the charge and discharge cycle process was repeated 200 times according to the above method, and the discharge capacity after 200 cycles was recorded.

[0079] Take 10 lithium-ion batteries from each group and calculate the average value of the capacity retention rate of the lithium-ion batteries. The cycle capacity retention rate of the lithium-ion battery = the discharge capacity (mAh) of the 200th cycle / the discharge capacity (mAh) after the first cycle × 100%.

[0080] 1.3 Cyclic thickness expansion rate test:

[0081] The thickness of lithium-ion batteries was tested using a 600g flat plate thickness gauge (ELASTOCON, EV 01).

[0082] The formed lithium ion batteries of the following embodiments and comparative examples were placed in a thermostat at 25°C ± 2°C for 2 hours, charged to 4.45V at a constant current of 0.7C, then charged to 0.05C at a constant voltage of 4.45V and left to stand for 15 minutes, and the thickness of the lithium ion battery in the fully charged state was recorded; then discharged to 3.0V at a constant current of 0.5C, which was one charge and discharge cycle process, and the thickness of the lithium ion battery in the first cycle of the lithium ion battery was recorded; then the charge and discharge cycle process was repeated 200 times according to the above method, and the thickness of the lithium ion battery after 200 cycles was recorded.

[0083] Take 10 lithium-ion batteries from each group and calculate the average value of the cycle thickness expansion rate of the lithium-ion battery. Cycle thickness expansion rate of lithium-ion battery = (thickness of lithium-ion battery at the 200th cycle / thickness of lithium-ion battery at the first cycle - 1) × 100%.

[0084] 2. Preparation method

[0085] 2.1 Preparation of positive electrode

[0086] The positive electrode active materials lithium iron phosphate (LiFePO4), conductive carbon black (Super P), and polyvinylidene fluoride (PVDF) are mixed in a weight ratio of 97.5:1.0:1.5, and N-methylpyrrolidone (NMP) is added as a solvent to prepare a slurry with a solid content of 0.75, and stirred evenly. The slurry is evenly coated on the positive electrode current collector aluminum foil and dried at 90°C. After cold pressing and cutting procedures, the positive electrode is cut into (14mm) specifications. The positive electrode loading is 1mAh / cm 2 .

[0087] 2.2 Preparation of electrolyte

[0088] In an environment with a water content of less than 10 ppm (in a dry argon atmosphere), dioxolane (DOL) and dimethyl ether (DME) are mixed in a volume ratio of 1:1, and then lithium salt LiN(SO2CF3)2 is added to an anhydrous solvent to dissolve and mix evenly, thereby obtaining an electrolyte with a lithium salt concentration of 1M.

[0089] 2.3 Preparation of negative electrode

[0090] Example 1

[0091] Using electrospinning technology, polyvinylidene fluoride is used as a precursor, and polyvinylidene fluoride is dissolved in 8mL of N,N-dimethylformamide and 2mL of acetone, wherein the weight ratio of polyvinylidene fluoride in the mixed solution is 8%, and the solution is fully stirred for 8 hours, and the solution is transferred to the syringe for electrospinning. The electrospinning process parameters are: negative pressure is -4kV, positive pressure is 18kV, liquid feed rate is 0.3mL / h, the distance between the collecting plate and the needle is 15cm-20cm, and the collection drum speed is 2000rpm. The polyvinylidene fluoride fiber prepared by electrospinning is placed in a vacuum drying oven at 80℃ for 12 hours. Using a three-dimensional skeleton composed of polyvinylidene fluoride fibers, the lithium metal film and the three-dimensional skeleton are pressed onto the copper foil current collector in sequence, wherein the three-dimensional skeleton is formed into a porous layer after a cold pressing process. Finally, the negative electrode cut into (18mm) specifications is directly punched out. Negative electrode structure measurement: the thickness of the porous layer is 50μm, the porosity is 80%, the diameter of a single fiber ranges from 0.4μm to 1μm, the thickness of the lithium metal film is 20μm, and the crystal phase structure in the polyvinylidene fluoride fiber is dominated by the β phase.

[0092] Example 2

[0093] The preparation method is substantially the same as that of Example 1, except that a pressure of 1 T is used in the cold pressing process, so that the thickness of the porous layer is 30 μm and the porosity is 40%.

[0094] Example 3

[0095] The preparation method is substantially the same as that of Example 1, except that the parameters used in the electrospinning process are: negative pressure of -1 kV, positive pressure of 8 kV, liquid feed rate of 0.8 mL / h, distance between the collecting plate and the needle of 12 cm, and collection drum speed of 100 rpm. Negative electrode structure measurement: porous layer thickness of 50 μm, porosity of 80%, single fiber diameter range of 0.4 μm to 1 μm, lithium metal film thickness of 20 μm, and the proportion of β phase in the crystalline structure of polyvinylidene fluoride fiber is lower than that of Example 1.

[0096] Example 4

[0097] The preparation method is roughly the same as that of Example 1, except that polymethyl methacrylate is used as the precursor. The parameters used in the electrospinning process are: negative pressure is -4kV, positive pressure is 12kV, liquid feed rate is 0.6mL / h, the distance between the collecting plate and the needle is 15cm-20cm; the collection drum speed is 2000rpm. A three-dimensional skeleton composed of polymethyl methacrylate fibers is used. Negative electrode structure measurement: the thickness of the porous layer is 50μm, the porosity is 80%, the diameter of a single fiber ranges from 0.4μm to 1μm, and the thickness of the lithium metal film is 20μm.

[0098] Example 5

[0099] The preparation method is substantially the same as that of Example 1, except that polyacrylonitrile is used as a precursor, polyacrylonitrile is dissolved in 10 mL of N,N-dimethylformamide, wherein the weight ratio of polyacrylonitrile in the mixed solution is 8%, and the parameters used in the electrospinning process are: voltage 12 kV, liquid feed rate 0.6 mL / h, distance between the collecting plate and the needle head 15 cm, and collection drum speed 2000 rpm. A three-dimensional skeleton composed of polyacrylonitrile fibers is used. Negative electrode structure measurement: porous layer thickness 50 μm, porosity 80%, single fiber diameter range 0.4 μm to 1 μm, lithium metal film thickness 20 μm.

[0100] Example 6

[0101] The preparation method is substantially the same as that of Example 1, except that the thickness of the porous layer is 300 μm.

[0102] Example 7

[0103] The preparation method is substantially the same as that of Example 1, except that the thickness of the porous layer is 500 μm.

[0104] Example 8

[0105] The preparation method is substantially the same as that of Example 1, except that the thickness of the porous layer is 200 μm.

[0106] Comparative Example 1

[0107] A 20μm lithium-copper composite tape is directly punched into (18mm) specifications and used as a negative electrode plate.

[0108] Comparative Example 2

[0109] A PP / PE / PP composite diaphragm is used as the porous layer. The lithium metal film and the PP / PE / PP composite diaphragm are pressed on the copper foil current collector in sequence by cold pressing, wherein the negative electrode cut into (18mm) specifications is obtained by direct punching. According to structural measurement, the porous layer composed of the PP / PE / PP composite diaphragm has a thickness of 20μm, a porosity of 30% to 50%, and a thickness of the lithium metal film of 20μm.

[0110] Comparative Example 3

[0111] Dissolve polyvinylidene fluoride in 10 mL of N-methylpyrrolidone, with the weight ratio of polyvinylidene fluoride in the mixed solution being 8%. After fully stirring for 4 hours, apply the slurry to the copper foil current collector; after coating, place the electrode in a vacuum drying oven at 80 degrees for 24 hours. Finally, press the lithium metal film onto the surface of the negative electrode by cold pressing, and directly punch out to obtain a negative electrode cut into (18 mm) specifications.

[0112] Comparative Example 4

[0113] The preparation method is substantially the same as that of Example 1, except that after the polyvinylidene fluoride fiber is kept at 80°C in a vacuum drying oven for 12 hours, the polyvinylidene fluoride fiber is further placed in a 230-degree muffle furnace for 2 hours, and placed in a high-purity argon tube furnace at 800 degrees for 6 hours to obtain carbonized polyvinylidene fluoride fiber, and a three-dimensional skeleton composed of carbonized polyvinylidene fluoride fiber is used. The negative electrode structure is measured, the porous layer thickness is 50μm, the porosity is 80%, the diameter of a single fiber ranges from 0.4μm to 1μm, and the thickness of the lithium metal film is 20μm.

[0114] 2.4 Preparation of lithium-ion batteries

[0115] A polyethylene film is used as a separator, wherein the thickness of the polyethylene film is 15 μm. The positive electrode, the separator and the negative electrode in the above embodiment are stacked in order, so that the separator is located between the positive electrode and the negative electrode to play an isolating role. The stacked electrode assembly is placed in an aluminum-plastic film package, and after dehydration at 80°C, a dry electrode assembly is obtained. Subsequently, the above electrolyte is injected into the dry electrode assembly, and after vacuum packaging, standing, formation, shaping and other processes, a button battery is assembled, that is, the preparation of the lithium-ion battery of the following embodiments and comparative examples is completed.

[0116] The negative electrode parameters of Examples 1-9 and Comparative Examples 1-3 and the structures that passed the lithium metal deposition test, the cycle performance test and the cycle thickness expansion rate test are recorded in Table 1 below.

[0117] Table 1

[0118]

[0119]

[0120] The results show that the present application can effectively improve the cycle performance of lithium-ion batteries and effectively suppress the cycle expansion rate of lithium-ion batteries by providing a negative electrode with a porous layer containing a three-dimensional skeleton. Specifically, it can be seen from Example 1 and Comparative Example 1 that the negative electrode with a three-dimensional skeleton proposed in the embodiment of the present application can greatly improve the volume expansion and cycle stability of the current lithium-copper composite belt, and reduce the cycle expansion rate of lithium-ion batteries to 15%.

[0121] It can be seen from Example 1 and Comparative Examples 2 and 3 that the porous layer of the embodiment of the present application has pores between fibers of good size and distribution due to its three-dimensional skeleton fiber structure, which is used to provide a storage space for lithium metal precipitation. In comparison, although the membranes in Comparative Examples 2 and 3 have a certain porosity, they cannot provide pores of sufficient size. Therefore, lithium metal cannot be precipitated in the pores of the membrane.

[0122] It can be seen from Example 1 and Comparative Example 4 that the three-dimensional skeleton of electrically insulating fibers can control the deposition position and deposition direction of lithium metal. The deposition of lithium metal in the three-dimensional skeleton of electronic conduction is random and tends to be deposited on the surface of the porous layer; the three-dimensional skeleton of electrical insulation can better control the deposition position, thereby inhibiting the volume expansion of the pole piece and improving the cycle performance of the battery.

[0123] The effect of the porosity of the porous layer on the precipitation of lithium metal can be seen from Examples 1 and 2. When the porosity is greater than 70%, most of the circulating lithium metal can enter the porous layer, so that the porous layer can better suppress the volume expansion of lithium metal and improve the electrochemical performance.

[0124] It can be seen from Examples 1 and 3 that by improving the crystal structure of the fiber material in the three-dimensional skeleton to make it present a β phase, the piezoelectric properties of the fiber structure can be optimized and the control of the cyclic expansion rate of the lithium-ion battery can be effectively improved.

[0125] It can be seen from Examples 1, 4 and 5 that different three-dimensional skeletons of fiber materials lead to different stability of the porous layer. The three-dimensional skeleton of polyvinylidene fluoride fiber is not easy to dissolve and expand in the electrolyte, so it can maintain a good three-dimensional structural morphology, so that the porous layer containing it has better cycle retention rate and volume expansion performance.

[0126] It can be seen from the above embodiments and comparative examples that the telephone device of the present application can effectively improve the lithium metal deposition on the negative electrode surface during the charge and discharge cycle of the electrochemical device by providing a porous layer including a three-dimensional skeleton and adopting an electrically insulating three-dimensional skeleton material; and inhibit the volume expansion of lithium metal; and at the same time slow down the growth of lithium dendrites, thereby improving the cycle performance, capacity performance and safety performance of the electrochemical device.

[0127] References to "embodiments", "partial embodiments", "one embodiment", "another example", "example", "specific example" or "partial example" throughout the specification mean that at least one embodiment or example in the present application includes the specific features, structures, materials or characteristics described in the embodiment or example. Therefore, descriptions appearing in various places throughout the specification, such as: "in some embodiments", "in an embodiment", "in one embodiment", "in another example", "in an example", "in a specific example" or "example", do not necessarily refer to the same embodiment or example in the present application. In addition, the specific features, structures, materials or characteristics herein may be combined in one or more embodiments or examples in any suitable manner.

[0128] Although illustrative embodiments have been demonstrated and described, those skilled in the art should understand that the above embodiments should not be construed as limitations on the present application, and that changes, substitutions and modifications may be made to the embodiments without departing from the spirit, principles and scope of the present application.

Claims

1. A negative electrode sheet, comprising: Anode current collector; and A porous layer, the porous layer is located on the negative electrode current collector, and the porous layer includes a three-dimensional skeleton containing electrically insulating fibers; Wherein, the fiber comprises a fluorine-containing polymer having a β phase. 2 . The negative electrode sheet according to claim 1 , wherein the porosity of the porous layer is greater than or equal to 70%. 3 . The negative electrode sheet according to claim 1 , wherein the diameter of the fiber is 50 nm to 10 μm. 4 . The negative electrode plate according to claim 1 , wherein the fibers in the three-dimensional skeleton are interwoven to form pores, and the pore size is 100 nm to 10 μm. 5 . The negative electrode sheet according to claim 1 , wherein the fibers include ion conductor fibers. 6 . The negative electrode sheet according to claim 1 , wherein the fiber has a hollow structure, wherein a pore size of the hollow structure is 10 nm to 500 nm.

7. The negative electrode plate according to claim 1, wherein the material of the fiber comprises one or more of a polymer material and an inorganic material, wherein the polymer material comprises one or more of the following components and derivatives of each component: polyvinylidene fluoride, polyimide, polyamide, polyacrylonitrile, polyethylene glycol, polyphenylene ether, polypropylene carbonate, polymethyl methacrylate, polyethylene terephthalate, polyethylene oxide, polyvinylidene fluoride-hexafluoropropylene or polyvinylidene fluoride-chlorotrifluoroethylene; and the inorganic material comprises one or more of sodium silicate, alumina and silicon oxide. The negative electrode sheet according to claim 1 , wherein the fiber comprises a material having piezoelectricity. 9 . The negative electrode sheet according to claim 1 , wherein the porous layer has a thickness of 30 μm to 500 μm. 10 . The negative electrode sheet according to claim 1 , further comprising lithium metal, wherein the lithium metal is located inside the porous layer or between the porous layer and the current collector.

11. An electrochemical device comprising: Positive electrode; Separator film; and A negative electrode sheet according to any one of claims 1 to 10.

12. The electrochemical device according to claim 11, wherein When the electrochemical device is fully charged, a thickness t of the lithium metal deposited portion is at least greater than or equal to 30% of a thickness T of the porous layer. 13 . An electronic device comprising the electrochemical device according to claim 11 .